Opportunities for respiratory disease transmission from people to chimpanzees at an East African tourism site. Issue 2 (5th January 2021) - Glasser, Darcey B.; Goldberg, Tony L.; Guma, Nelson; Balyesiima, Godfrey; Agaba, Hillary; Gessa, Simplicious J.; Rothman, Jessica M.
Abstract: Respiratory illnesses, including COVID‐19, present a serious threat to endangered wild chimpanzee ( Pan troglodytes ) populations. In some parts of sub‐Saharan Africa, chimpanzee tracking is a popular tourism activity, offering visitors a chance to view apes in their natural habitats. Chimpanzee tourism is an important source of revenue and thus benefits conservation; however, chimpanzee tracking may also increase the risk of disease transmission from people to chimpanzees directly (e.g., via aerosol transmission) or indirectly (e.g., through the environment or via fomites). This study assessed how tourist behaviors might facilitate respiratory disease transmission at a chimpanzee tracking site in Kibale National Park, Uganda. We observed tourists, guides, and student interns from the time they entered the forest to view the chimpanzees until they left the forest and noted behaviors related to disease transmission. Common behaviors included coughing, sneezing, and urinating, which respectively occurred during 88.1%, 65.4%, and 36.6% of excursions. Per excursion, individuals touched their faces an average of 125.84 ± 34.45 times and touched large tree trunks or branches (which chimpanzees might subsequently touch) an average of 230.14 ± 108.66 times. These results show that many pathways exist by which pathogens might move from humans to chimpanzees in the context of tourism. Guidelines for minimizing the risk of such transmission should consider tourist behavior and the full range of modes by which pathogen transmission might occur between tourists and chimpanzees. Abstract : Chimpanzee (Pan troglodytes) observed during study. Highlights: Great ape tourism presents risk for reverse zoonotic infection. Future guidelines for great ape tourism should take into consideration the behavioral propensities of individual tourists.